Why bother? Student motivation to participate in student evaluations of teaching. Issue 3 (3rd April 2019) - Hoel, Anniken; Dahl, Tove Irene
Abstract: When response rates on student evaluations of teaching (SETs) are low, inability to properly interpret and use responses from the students who do participate is a big problem. Where does the motivation to participate break down, and where and how does it make sense to invest efforts in rectifying that? In this study, we examined 641 university students' reported behaviours and motivation related to their SET participation. In terms of behaviour, students who seldom or never participate in online SET tools reported a willingness to invest, at most, five minutes in the process, though the majority never even open the online evaluation links when they receive them. In terms of motivation, they significantly differed from students who always participate with distinctly lower levels of: (1) willingness to participate at all, (2) perception of autonomy and competence, (3) meaningfulness, (4) personal value, (5) engagement in others' participation, and (6) understanding of the value of their own participation for others' benefit. Based on these findings, we propose a strategy for increasing future response rates, particularly among recalcitrant students, in order to be able to gather sufficient and reliable results for the work of improving teaching.